Prevalence and Correlates of HIV-Associated Neurocognitive Disorders (HAND) in Northwestern Nigeria - Ahmad M. Yakasai; Mustafa I. Gudaji; Hamza Muhammad; Aliyu Ibrahim; Lukman F. Owolabi; Daiyabu A. Ibrahim; Musa Babashani; Muhammad S. Mijinyawa; Musa M. Borodo; Abayomi S. Ogun; Abdulrazaq G. Habib (Neurology Research International)
HIV-associated Neurocognitive Disorders (HAND) are common among HIV-positive individuals. This study explored the prevalence and correlates of HAND in Nigeria. 80 HIV-positive and 40 HIV-negative adults selected from Aminu Kano Teaching Hospital (AKTH) received comprehensive evaluations. A multidomain neuropsychological test (MDNPT) battery assessing 7 domains was administered to the participants and their performance was combined with measures of functional status to classify impairments into various grades of HAND. Univariate and multivariate analyses were performed to identify correlates of symptomatic HAND. Among the HIV-positive individuals, 50% were highly active antiretroviral therapy-experienced (HAART+) and 50% were highly active antiretroviral therapy naive (HAART−). Symptomatic HAND was found among 40% of the HAART− individuals and 30% of the HAART+ individuals. Respective prevalence of HIV-associated dementia (HAD) was 23% and 5%, respectively (p=0.0002). In a binary logistic regression model, only fewer years of education independently predicted symptomatic HAND [Odds Ratio (OR) = 1.2, 95% confidence interval (CI) = 1.04–1.44, p=0.016]. The prevalence of HAND in Nigeria is high with HAD being commoner among HAART− patients. Provision of HAART and strict monitoring of patients at risk of HAND are needed to scale down the burden of the disease.